Role of B Cell Profile for Predicting Secondary Autoimmunity in Patients Treated With Alemtuzumab - Walo-Delgado, Paulette Esperanza; Monreal, Enric; Medina, Silvia; Quintana, Ester; Sainz de la Maza, Susana; Fernández-Velasco, José Ignacio; Lapuente, Paloma; Comabella, Manuel; Ramió-Torrentà, Lluis; Montalban, Xavier; Midaglia, Luciana; Villarrubia, Noelia; et al. (Frontiers in Immunology, 2021)
Objective To explore if baseline blood lymphocyte profile could identify relapsing remitting multiple sclerosis (RRMS) patients at higher risk of developing secondary autoimmune adverse events (AIAEs) after alemtuzumab treatment. Methods Multicenter prospective study including 57 RRMS patients treated with alemtuzumab followed for 3.25 [3.5-4.21] years, (median [interquartile range]). Blood samples were collected at baseline, and leukocyte subsets determined by flow cytometry. We had additional samples one year after the first cycle of alemtuzumab treatment in 39 cases. Results Twenty-two patients (38.6%) developed AIAEs during follow-up. They had higher B-cell percentages at baseline (p=0.0014), being differences mainly due to plasmablasts/plasma cells (PB/PC, p=0.0011). Those with no AIAEs had higher percentages of CD4+ T cells (p=0.013), mainly due to terminally differentiated (TD) (p=0.034) and effector memory (EM) (p=0.031) phenotypes. AIAEs- patients also showed higher values of TNF-alpha-producing CD8+ T cells (p=0.029). The percentage of PB/PC was the best variable to differentiate both groups of patients. Baseline values >0.10% closely associated with higher AIAE risk (Odds ratio [OR]: 5.91, 95% CI: 1.83-19.10, p=0.004). When excluding the 12 patients with natalizumab, which decreases blood PB/PC percentages, being the last treatment before alemtuzumab, baseline PB/PC >0.1% even predicted more accurately the risk of AIAEs (OR: 11.67, 95% CI: 2.62-51.89, p=0.0007). The AIAEs+ group continued having high percentages of PB/PC after a year of alemtuzumab treatment (p=0.0058). Conclusions A PB/PC percentage <0.1% at baseline identifies MS patients at low risk of secondary autoimmunity during alemtuzumab treatment.​